The Impact of International Trade Wars on the Economic Stability of Developing Countries - Barreto, Ananias (Nomico, 2025)
This study investigates the impact of international trade wars on the economic stability of developing countries, with a particular focus on the indirect consequences of the U.S.–China trade conflict between 2015 and 2023. Utilizing a quantitative-explanatory research design and panel data analysis covering selected developing countries, the research explores how trade tensions between global powers trigger macroeconomic instability in non-combatant nations. The results demonstrate that trade wars significantly influence key indicators such as GDP growth, inflation, exchange rate volatility, current account balances, and foreign direct investment inflows. The study finds that countries with a high dependency on exports to China or the U.S. are more exposed to economic disruptions, particularly if they lack strong institutional frameworks or macroeconomic buffers. Regional differences and economic structure also shaped the severity of the impacts. The findings highlight the importance of export diversification, institutional strengthening, and regional trade cooperation as strategies to mitigate external shocks. This research contributes to the existing literature by providing empirical evidence on third-party vulnerabilities in an increasingly fragmented global trade system.